Analisis Manajemen Tabungan Wadi’ah Pelajar pada PT BPRS Sungai Pua Syariah Ditinjau dari Manajemen Bank Syariah - Nanda Reza Safitri; Rini Elvira; Imamuddin Imamuddin; Gusrianti Gusrianti (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
This study is motivated by the critical importance of consistently implementing sharia principles in all Islamic banking products, including wadi’ah-based savings. The research aims to describe the management practices of student wadi’ah savings at PT BPRS Sungai Pua Syariah and evaluate their alignment with the principles of Islamic bank management. A descriptive qualitative approach was employed, utilizing data collection techniques such as observation, structured interviews, and document analysis. The key informants in this study were the Director and the Head of Operations at PT BPRS Sungai Pua Syariah. The findings reveal that the management of student wadi’ah savings at the bank has generally implemented core management functions planning, organizing, execution, and control—effectively. However, the study also identified a deviation from the fundamental principles of the wadi’ah contract, whereby the bank distributes profit-sharing to wadi’ah savings holders, which contradicts the nature of a pure safekeeping agreement. This indicates the need for a thorough evaluation and realignment of savings management practices to ensure greater compliance with sharia principles.